An Outline of the Political Life of Lithuanian Ethnic Minority in Poland as Reported in the KGB File “Pass-Bridge” - Banionis, Juozas (Genocidas ir rezistencija, 1998)
The aim of this article is to shed light on the role of the so–called Suwalki Triangle of the 1980s, consisting of our autochthonous compatriots living between Suwalki, Sejny and Punsk, in the cause of Lithuanian freedom aspired by the diaspora. At the same time, an attempt was made to describe the sentiments of Polish Lithuanians and their attitude towards Soviet Lithuania.